Pengaturan Penggunaan Tanah Adat Melalui HPL sebagai Alat untuk Menguatkan Posisi Masyarakat Adat - Lenny Husna (IPMHI Law Journal, 2025)
The Right of Management (Hak Manajemen/HPL) constitutes a strategic issue within the Indonesian agrarian legal system, as it directly relates to the recognition and protection of indigenous peoples' rights. Regulatory developments reveal persistent tension between state authority and the collective rights of indigenous communities in controlling and using customary land. This study aims to analyze the normative construction of HPL over customary land and to formulate a reconstructed regulatory model positioning HPL as an instrument to strengthen the legal standing of indigenous peoples. The research employs normative legal methodology, using statutory, conceptual, and analytical approaches, supported by primary and secondary legal materials and examined through prescriptive legal analysis. The findings demonstrate that the current construction of HPL still places the state in a dominant position and has not fully affirmed indigenous communities as legal subjects with full legal capacity. Normative ambiguities remain regarding the limits of authority, mechanisms for recognizing customary institutions, and the equitable distribution of economic benefits. Regulatory reconstruction is therefore required through the integration of distributive justice principles, legal pluralism, mandatory indigenous consent, and an equal, transparent tripartite partnership model. HPL must function as a substantive empowerment instrument accompanied by sustainable social and ecological safeguards within a welfare state framework